A highly spatially resolved GIS-based model to assess the isoprenoid emissions from key Italian ecosystems - Pacheco, Claudia Kemper; Fares, Silvano; Ciccioli, Paolo (Atmospheric Environment, 2014)
The amount of Biogenic Volatile Organic Compounds (BVOC) emitted from terrestrial vegetation is of great importance in atmospheric reactivity, particularly for ozone-forming reactions and as condensation nuclei in aerosol formation and growth. This work presents a detailed inventory of isoprenoid emissions from vegetation in Italy using an original approach which combines state of the art models to estimate the species-specific isoprenoid emissions and a Geographic Information System (GIS) where emissions are spatially represented. Isoprenoid species and basal emission factors were obtained by combining results from laboratory experiments with those published in literature. For the first time, our investigation was not only restricted to isoprene and total monoterpenes, but our goal was to provide maps of isoprene and individual monoterpenes at a high-spatial (∼1 km2) and temporal resolution (daily runs, monthly trends in emissions are discussed in the text). Another novelty in our research was the inclusion of the effects of phenology on plant emissions. Our results show that: a) isoprene, a-pinene, sabinene and b-pinene are the most important compounds emitted from vegetation in Italy; b) annual biogenic isoprene and monoterpene fluxes for the year 2006 were ∼31.30 Gg and ∼37.70 Gg, respectively; and c) Q. pubescens+Q. petrea+Q. robur, Q. ilex, Q. suber and Fagus sylvatica are the principal isoprenoid emitting species in the country. The high spatial and temporal resolution, combined with the species-specific emission output, makes the model particularly suitable for assessing local budgets, and for modelling photochemical pollution in Italy.
Keywords: BVOC inventory; isoprene; Isoprenoids; Italian forests; Monoterpenes

Observations of Diurnal to Weekly Variations of Monoterpene-Dominated Fluxes of Volatile Organic Compounds from Mediterranean Forests: Implications for Regional Modeling - Fares, Silvano; Schnitzhofer, Ralf; Jiang, Xiaoyan; Guenther, Alex; Hansel, Armin; Loreto, Francesco (ENVIRONMENTAL SCIENCE & TECHNOLOGY, 2013)
The Estate of Castelporziano (Rome, Italy) hosts many ecosystems representative of Mediterranean vegetation, especially holm oak and pine forests and dune vegetation. In this work, basal emission factors (BEFs) of biogenic volatile organic compounds (BVOCs) obtained by Eddy Covariance in a field campaign using a proton transfer reaction-time-of-flight-mass spectrometer (PTR-TOF-MS) were compared to BEFs reported in previous studies that could not measure fluxes in real-time. Globally, broadleaf forests are dominated by isoprene emissions, but these Mediterranean ecosystems are dominated by strong monoterpene emitters, as shown by the new BEFs. The original and new BEFs were used to parametrize the model of emissions of gases and aerosols from nature (MEGAN v2.1), and model outputs were compared with measured fluxes. Results showed good agreement between modeled and measured fluxes when a model was used to predict radiative transfer and energy balance across the canopy. We then evaluated whether changes in BVOC emissions can affect the chemistry of the atmosphere and climate at a regional level. MEGAN was run together with the land surface model (community land model, CLM v4.0) of the community earth system model (CESM v1.0). Results highlighted that tropospheric ozone concentration and air temperature predicted from the model are sensitive to the magnitude of BVOC emissions, thus demonstrating the importance of adopting the proper BEF values for model parametrization.
The following values have no corresponding Zotero field: pub-location: 1155 16TH ST, NW, WASHINGTON, DC 20036 USA publisher: AMER CHEMICAL SOC
Keywords: Emissions; GLOBAL-MODEL; Ozone; PROTON-TRANSFER REACTION; PTR-TOF; QUERCUS-ILEX; REACTION MASS-SPECTROMETRY

Volatile organic compounds from Italian vegetation and their interaction with ozone. - Calfapietra, Carlo; Fares, Silvano; Loreto, Francesco (Environmental pollution (Barking, Essex : 1987), 2009)
Volatile Organic Compounds (VOCs) emitted from vegetation (particularly isoprenoids) represent an important source of atmospheric hydrocarbons almost double the anthropogenic source. When biogenic VOC mix with NO(x) in the presence of UV radiation, ozone (O(3)) is formed. In Italy, optimal conditions for O(3) formation in terms of VOC/NO(x) ratios and abundance of UV radiation occur for long periods of the year. Moreover, Italian vegetation includes several species that are strong and evergreen isoprenoid emitters, and high temperatures for part of the year further stimulate these temperature-dependent emissions. We review emission of isoprenoids from Italian vegetation, current knowledge on the impact of rising O(3) levels on isoprenoid emission, and evidence showing that isoprenoids can increase both the O(3) flux to the plant and protection against oxidative stress because of their antioxidant functions. This trait not only influences plant tolerance to O(3) but also may substantially alter the flux of O(3) between atmosphere and biosphere.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd accession-num: 19019511
Keywords: antioxidant; isoprene; Monoterpene; Ozone flux; VOC

Physiological responses of Quercus ilex Leaves to Water Stress and Acute Ozone Exposure Under Controlled Conditions - Vitale, Marcello; Salvatori, Elisabetta; Loreto, Francesco; Fares, Silvano; Manes, Fausto (Water, Air, and Soil Pollution, 2007)
The combined effect of water stress and ozone (O3) on stomatal O3 flux, damage to photosynthesis, and detoxification by biogenic volatile organic compounds (BVOC) in Quercus ilex leaves was studied. A 4-weeks O3 exposure (250 ppb, 4 h per day) caused a reduction of photosynthesis and stomatal conductance, which was fully recovered 1 week after the end of the treatment, in well-watered and water-stressed plants. Measurements of stomatal O3 flux revealed a low stomatal flux of the pollutant, which became minimal after stomatal closure caused by water stress. An induction of volatile monoterpenes, important compounds in the O3 scavenging system in Q. ilex, and a burst of lipoxygenase compounds (LOX), which are released as gaseous by-products of membrane peroxidation, was observed after 2–3 weeks of O3 fumigation. However, these compounds were also released in control leaves that were exposed to ozone only briefly, to determine stomatal O3 flux. The low stomatal flux that occurred in water stress conditions helped avoiding permanent damage to Q. ilex leaves, although during the O3 treatment photosynthesis was severely limited by stomatal closure. In well-watered plants, O3 fumigation caused a noticeable increase of nocturnal stomatal conductance. If confirmed on adult plants under field conditions, this effect can imply larger flux of O3 at night and possible detrimental effects of O3 on leaf functions in plants exposed to high nocturnal O3 levels.
Keywords: Gas exchange; Holm oak (Quercus ilex); lipoxygenase products; monoterpene emission; o3 flux; photosynthesis; Stomatal conductance

Physiological responses of Quercus ilex Leaves to Water Stress and Acute Ozone Exposure Under Controlled Conditions - Vitale, Marcello; Salvatori, Elisabetta; Loreto, Francesco; Fares, Silvano; Manes, Fausto (Water, Air, and Soil Pollution, 2007)
The combined effect of water stress and ozone (O3) on stomatal O3 flux, damage to photosynthesis, and detoxification by biogenic volatile organic compounds (BVOC) in Quercus ilex leaves was studied. A 4-weeks O3 exposure (250 ppb, 4 h per day) caused a reduction of photosynthesis and stomatal conductance, which was fully recovered 1 week after the end of the treatment, in well-watered and water-stressed plants. Measurements of stomatal O3 flux revealed a low stomatal flux of the pollutant, which became minimal after stomatal closure caused by water stress. An induction of volatile monoterpenes, important compounds in the O3 scavenging system in Q. ilex, and a burst of lipoxygenase compounds (LOX), which are released as gaseous by-products of membrane peroxidation, was observed after 2–3 weeks of O3 fumigation. However, these compounds were also released in control leaves that were exposed to ozone only briefly, to determine stomatal O3 flux. The low stomatal flux that occurred in water stress conditions helped avoiding permanent damage to Q. ilex leaves, although during the O3 treatment photosynthesis was severely limited by stomatal closure. In well-watered plants, O3 fumigation caused a noticeable increase of nocturnal stomatal conductance. If confirmed on adult plants under field conditions, this effect can imply larger flux of O3 at night and possible detrimental effects of O3 on leaf functions in plants exposed to high nocturnal O3 levels.
Keywords: Gas exchange; Holm oak (Quercus ilex); lipoxygenase products; monoterpene emission; o3 flux; photosynthesis; Stomatal conductance